Influencer Credibility and FOMO as Drivers of Impulsive Buying: Mediating Role of Trust and Hedonic Motivation - Chrivana O. Timbuleng; Ronny H. Walean; Deske W. Mandagi (Yayasan Pendidikan Bukhari Dwi Muslim, 2026)
Purpose: This study aims to examine the direct and indirect effects of Fear of Missing Out (FOMO) and influencer credibility on impulsive buying, with hedonic motivation and trust serving as mediating variables. Research Method: A quantitative research design was employed using survey data collected from 200 active TikTok Shop users in North Sulawesi, Indonesia, and analyzed using Structural Equation Modeling (SEM) with SmartPLS 4.0. Results and Discussion: The findings indicate that FOMO has a significant direct effect on impulsive buying, while hedonic motivation partially mediates this relationship. In contrast, influencer credibility does not directly influence impulsive buying; instead, it exerts an indirect effect through trust, which fully mediates the relationship. These results reveal two distinct psychological pathways: an affective pathway in which FOMO enhances hedonic motivation, leading to impulsive buying, and a cognitive pathway in which influencer credibility builds trust that subsequently drives impulsive buying. Implications: This study contributes to the social commerce literature by advancing a dual-mediation framework in explaining impulsive buying behavior and offers practical implications for marketers to design more effective short-video campaigns by leveraging emotional triggers such as FOMO and strengthening credibility through trust.